2007
DOI: 10.3174/ajnr.a0634
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Spinal Epidural Collections after Lumbar Puncture in Children

Abstract: BACKGROUND AND PURPOSE:Complications from lumbar puncture (LP) include headache; mild puncture-site pain; and, rarely, subdural, epidural, or subarachnoid hemorrhage. In infants, asymptomatic leakage of CSF documented with ultrasound is common. We report the MR imaging findings and clinical course of 25 symptomatic patients with spinal epidural collections after LP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…12 Strupp et al 13 demonstrated that stylet reinsertion before spinal needle removal significantly reduced the occurrence of post-lumbar puncture symptoms. In 1 retrospective study, the number of lumbar puncture attempts did not correlate with the size of the epidural CSF collection, 14 which was true in our patient. Finally, although our patient remained supine for 3 hours postprocedure, recumbent positioning has not been proven to reduce post-lumbar puncture symptoms.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…12 Strupp et al 13 demonstrated that stylet reinsertion before spinal needle removal significantly reduced the occurrence of post-lumbar puncture symptoms. In 1 retrospective study, the number of lumbar puncture attempts did not correlate with the size of the epidural CSF collection, 14 which was true in our patient. Finally, although our patient remained supine for 3 hours postprocedure, recumbent positioning has not been proven to reduce post-lumbar puncture symptoms.…”
Section: Discussionmentioning
confidence: 45%
“…15 Evaluation of the symptomatic patient after a lumbar puncture should begin with a thorough neurologic examination. Magnetic resonance imaging can delineate the size and signal intensity of the collection, 14 although it may be difficult to radiographically differentiate CSF, blood, and pus. Our patient presented with fever, which raised suspicion of an epidural abscess and necessitated laminectomy by neurosurgery for definitive diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Koch et al . [3] found that MR studies in 25 pediatric patients (average age 5 years, 1 month old) undergoing LPs had epidural CSF collections on MR scans; symptoms also fully resolved with conservative treatment. When Amini et al .…”
Section: Discussionmentioning
confidence: 99%
“…Infection and shunt dysfunction are very rare consequences of the implantation. However, epidural, subdural, subarachnoid and intracerebral hemorrhages have been cited as rare complications of lumbar punctures [3]. Cerebrospinal fluid fistulas primarily occur in children [4].…”
Section: Introductionmentioning
confidence: 99%